Investigation of the 2nd generation of intact stability criteria for ships vulnerable to parametric rolling in following seas - Krüger, Stefan; Hatecke, Hannes; Billerbeck, Heike; Bruns, Anna; Kluwe, Florian (Volume 5: Ocean Engineering, 2013)
The existing IMO intact stability criteria (IS-Code 2008) do not generally provide sufficient safety against dynamic stability failures such as parametric rolling for modern ships. Therefore, new stability criteria have been developed by IMO / SLF. These so-called Second Generation Stability Criteria shall ensure sufficient dynamic stability. The criteria are structured in a three level approach, where the first level consists of quite simple formulae. If a ship does not pass the first level, it is assumed that the ship is vulnerable to the phenomenon addressed, and the second level of criteria shall then be applied. This level consists of computations which are a little more complex, but they still treat the problems addressed in a strongly simplified manner. If now the ship does not pass the second level, a third level shall be applied to ensure that the ship can be designed and operated safely. This third level consists of direct calculation methods which shall be applied, however no criteria or procedures have yet been developed for this third level. We have applied the level 1 and level 2 criteria to a reference ship where a direct stability assessment has been performed during the design. The results showed extremely large scatter in the required GM-values of the criteria, and none of the criteria showed GM values roughly comparable to the direct assessment. The paper shows why the application of the criteria is challenging for the design of RoRo-ships and why a third level (direct assessment) is urgently required before the first two levels are put into force. Some conclusions are also drawn for the possible treatment of the new criteria in a stability booklet.